Comparative Transcriptome Analysis Reveals Key Pathways and Hub Genes in Rapeseed During the Early Stage of Plasmodiophora brassicae Infection - Li, Lixia; Long, Ying; Li, Hao; Wu, Xiaoming (Frontiers in Genetics, 2020)
Rapeseed (Brassica napus L., AACC, 2n=38) is one of the most important oil crops around the world. With intensified rapeseed cultivation, the incidence and severity of clubroot infected by Plasmodiophora brassicae Wor. (P. brassicae) has increased very fast, which seriously impedes the development of rapeseed industry. Therefore, it is very important and timely to investigate the mechanisms and genes regulating clubroot resistance (CR) in rapeseed. In this study, comparative transcriptome analysis was carried out on two rapeseed accessions of R- (resistant) and S- (susceptible) line. 3,171 and 714 differentially expressed genes (DEGs) were detected in the R- and S-line compared with the control groups, respectively. The results indicated that the CR difference between the R- and S-line had already shown during the early stage of P. brassicae infection and the change of gene expression pattern of R-line exhibited a more intense defensive response than that of S-line. Moreover, KEGG analysis of 2,163 relative-DEGs, identified between the R- and S-line, revealed that genes participated in plant hormone signal transduction, fatty acid metabolism, and glucosinolate biosynthesis were involved in regulation of CR. Further, twelve hub genes were identified from all relative-DEGs with the help of weighted gene co-expression network analysis. Haplotype analysis indicated that the natural variations in the coding regions of some hub genes also made contributed to CR. This study not only provides valuable information for CR molecular mechanisms, but also has applied implications for CR breeding in rapeseed.